Pengaruh Penambahan Stabilizer Alami Berbasis Umbi Lokal untuk Peningkatan Sifat Fisik dan Kimia Es Krim Buah Naga Merah (Hylocereus polyrhizus Sp.) - Nofrida, Rini; Sulastri, Yeni; Widyasari, Rucitra; Zaini, M. Abbas; Nasrullah, Arif (Jurnal Ilmiah Teknologi Pertanian Agrotechno; Vol 3 No 1 (2018)DO - 10.24843/JITPA.2018.v03.i01.p06, 2018)
Ice cream is a kind of dessert with a sweet taste and served in a cold and frozen. Ice cream has a soft texture, to make the texture required stabilizer, which is one of the ingredients added in the manufacture of ice cream in order to prevent crystallization, as a binder and improve the texture. Stabilizers can be met from starch-based materials of local potency of tubers. Gelatinization of starch in the tuber flour can replace the function of the stabilizer. Some types of tubers that can be developed as an alternative source of natural stabilizer such as porang, uwi, and taro. The study is entitled "The Effect of Adding Natural Stabilizer Based on local tubers for Improving physical and chemical properties of Red Dragon Fruit Ice Cream(Hylocereus polyrhizus sp)". This study aims to examine the effect of local tubers (lombos,flour (porang), uwi flour and belitung taro flour) as a stabilizer on manufacture dragon fruit ice cream. The research will be done first with the preparation stage which is the manufacture of tuber flours (porang, uwi and Belitung taro). Implementation of the research was conducted in two stages are 1) making dragon fruit ice cream with tuber flours; 2) determining the best treatment of the use of stabilizer from the tubers. The tests include the physical and chemical quality that has been performed in the Quality Control Laboratory, the Chemical Laboratory and the Food Biochemistry and the Food Processing Laboratory. Parameters observed in this study include moisture content, total dissolved solids, melting time, emulsion stability, and texture. Based on the results of the research known that the best treatment is the use of porang stabilizer with 0.5% concentration in the manufacture of red dragon fruit ice cream. The treatment is able to match the ability of CMC as an ice cream stabilizer. In the treatment porang 0.5% obtained water content 64.39%, total soluble solids 14.80%, emulsion stability 87.41%, and  melting time 95.45 minutes / 100 grams.